A longitudinal investigation of quality of life and negative emotions in misophonia - Dibb, Bridget; Golding, Sarah E. (Frontiers in Neuroscience, 2022)
Aims: This longitudinal study examined the role of anger, disgust and anxiety in the experience of misophonia, the quality of life of those with self-reported misophonia in comparison to those without misophonia, and the association of misophonia and quality of life over time. Methods: An online longitudinal survey was conducted, with misophonia, anger, disgust, anxiety, depression, self-esteem and quality of life measured at two time points (6-months apart) in two groups of people (those with self-reported misophonia and those without misophonia). Results: Anger and disgust emerged as the primary predictors of misophonic responses. Anxiety and depression were not significantly associated with misophonia over time. Differences in quality of life were observed between those with and without self-reported misophonia in the current study, with lower scores across the SF-36 domains of role limitations due to emotional problems, energy/fatigue, emotional wellbeing, social functioning, and general health for those with misophonia compared to those without misophonia. Compared with other studies, scores for those with self-reported misophonia were lower than those with long-term physical conditions, similar to those with tinnitus, but higher than those with obsessive compulsive disorder. Misophonia was predictive of quality of life over time but only on two domains: role limitations due to emotional problems (predictors: avoidance, emotional responses, and impact on participation in life) and pain (predictor: impact on participation in life). Depression remained a strong predictor of quality of life over time. Conclusions: Anger and disgust are more strongly associated with the experience of misophonia than anxiety. Quality of life in people with self-reported misophonia is lower than in the general population and may be similar to those with tinnitus. Depression, avoiding triggers, the extent of the emotional response, and perceived impact on participation in life are associated with perceptions of lower quality of life over time for people with self-reported misophonia.